Flow cytometry-based monitoring of myeloid-derived suppressor cells in the peripheral blood of patients with solid tumors - Donaubauer, Anna-Jasmina; Scheer, Ilka; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Academic Press Inc., 2025)
Myeloid-derived suppressor cells (MDSCs) ameliorate inflammation by inhibiting T cell responses. In pathological conditions, such as autoimmunity, chronic infections or cancer they accumulate in the periphery. In cancer, MDSCs can also be part of the tumor microenvironment and are associated with a worse prognosis and limited response to immunotherapy. Nowadays attempts are made to specifically target MDSCs in cancer therapy. Still, the role of MDSCs in standard cancer treatment modalities, such as radiotherapy remains mostly elusive. Here, we describe a flow cytometry-based method to determine and monitor monocytic and granulocytic-derived MDSCs directly from whole blood in an easy, fast and reliable assay. As specific surface markers for MDSCs are lacking, the assay follows a gating strategy that excludes successively the main immune cells types and analyzes the remaining events for a set of molecules that are expressed on MDSCs. This assay is especially appropriate for longitudinal analyses and clinical trials and is suitable for being integrated into more complex immunophenotyping panels to generate a comprehensive immune status.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Flow cytometry; Immune monitoring; Immune status; Immunophenotyping; Myeloid-derived suppressor cells